The Qualitative Stability and Thermal Properties Investigation of TiO2-EG/W Nanofluids Through Experimental Validation - Muhamad Taufik Ulhakim; Sukarman; Khoirudin; Nazar Fazrin; Tomas Irfani; Amri Abdulah (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2024)
Over the past two decades, researchers have been extremely interested in developing TiO2 nanofluids for heat exchanger applications. Therefore, this study evaluates the performance of employing TiO2 nanofluids, which were prepared using ethylene glycol (EG) and distilled water as the base fluid, then called TiO2-EG/W. The qualitative stability and thermal conductivity properties were measured through the experimental investigation. XRD and SEM analyses were also carried out to investigate the structures of TiO2 nanoparticles used in terms of their crystalline and morphological structures. The results showed a positive impact of stability even for 15 days, and after that, the nanoparticles dropped to the sedimentation by about 58%. Then, the highest thermal conductivity at the temperature of 80 °C was increased by about 17.08% compared to the base fluid. Supported by the results of XRD and SEM analysis, respectively, highlight that TiO2 nanoparticles have a rutile phase with an average crystallite size of 20.23 nm and are small spherical in morphology. This paper also provided the challenge and future perspective of TiO2 nanofluid to appear as an innovation for the development of TiO2 nanofluid in the further studies of heat exchanger applications.